Hydrogen adsorption on Ni doped carbon nanocone - Köse, Ahmet; Yüksel, Numan; Fellah, Mehmet Ferdi (ELSEVIER SCIENCE SA, 2022)
Hydrogen adsorption was investigated on Ni doped carbon nanocone (Ni-CNC) 180 degrees C by Density Functional Theory (DFT). The WB97XD method was used with the 6-31G(d,p) and LanL2DZ basis sets. The electronegativity, HOMO and LUMO energies, chemical hardness, chemical potential, adsorption enthalpy and adsorption energy values have been calculated for hydrogen adsorption on Ni-CNC structure. The adsorption enthalpy value of hydrogen molecule was calculated as-27.8 kJ/mol. According to the storage capacity study for the Ni-CNC structure, it was found that this structure adsorbed eight hydrogen molecules and the hydrogen storage capacity was calculated to be similar to 4.3 wt%. After hydrogen adsorption, there was no significant decrease in HOMO-LUMO gap value. In addition, this situation indicates that the electrical conductivity of the Ni-CNC structure does not increase. These results show that the Ni-CNC structure cannot be used as a sensor for the hydrogen molecule, but it is a promising candidate material for hydrogen storage at room temperature.
Keywords: Adsorption; Hydrogen; Storage; DFT; Nanocone; Ni atom